If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M(3m + 1) = 0 Reorder the terms: M(1 + 3m) = 0 (1 * M + 3m * M) = 0 (1M + 3mM) = 0 Solving 1M + 3mM = 0 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'M'. M(1 + 3m) = 0Subproblem 1
Set the factor 'M' equal to zero and attempt to solve: Simplifying M = 0 Solving M = 0 Move all terms containing M to the left, all other terms to the right. Simplifying M = 0Subproblem 2
Set the factor '(1 + 3m)' equal to zero and attempt to solve: Simplifying 1 + 3m = 0 Solving 1 + 3m = 0 Move all terms containing M to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3m = 0 + -1 3m = 0 + -1 Combine like terms: 0 + -1 = -1 3m = -1 Add '-3m' to each side of the equation. 3m + -3m = -1 + -3m Combine like terms: 3m + -3m = 0 0 = -1 + -3m Simplifying 0 = -1 + -3m The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
M = {0}
| .5x-3=2.25+1.5x | | 1.5x+14=30 | | 6x^2+13+6=0 | | 8(w-4)=32 | | 5x-2=8x+6 | | 4(3x-8)-11x=2 | | 2y=8x+20 | | 72w^4-32w^2= | | -9f=72-f | | (x^2+4x)+(y^2-12y)=-24 | | 4n+2.5=7.3 | | 3x+50=6x | | 2x^2-8x-16y-24=0 | | -34+22=-3x+9x | | x-3/5=1/15 | | 44-50=x | | -76=(-2/3) | | 15c-8-3x=16 | | 4x^3+24x^2+36x=0 | | -3.4x-3=-2.9x+2 | | 3x+45=76,5 | | 2x^3-12x^2+18x+45=0 | | 4x^2-9=3x^2 | | d-3=-17 | | -3x+5+4x=-22+19 | | 24t^2-10t-4=0 | | x^2+1=x^2-6 | | -3(4s-3)-9=-2(8s+5)-3 | | 8(a+b)=(a+b)8 | | rx^2+sx+t=0 | | -12+y=24+-9 | | 3x+6=2x^2+4 |